2015
DOI: 10.1177/082585971503100403
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia in a Palliative Care Setting — A Coordinated Overview of Caregivers' Responses to Dietary Changes: The DysCORD Qualitative Study

Abstract: Primary caregivers (PCGs) are closely involved in preparing meals and feeding patients who are at the end of life, yet their responses to patients' swallowing difficulties have not been extensively analyzed. This study aimed to reach an understanding of PCGs' beliefs, values, and responses to dysphagia and dietary modifications in the palliative care setting. A total of 14 PCGs were interviewed and asked to share their thoughts and feelings about patients' dysphagia symptoms and the diet changes resulting from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…Support for a focus on individual choices and quality of life was strongly indicated by the current study, which further identified the need for clinician self‐care and de‐briefing in this complex clinical area. In the dementia literature in particular, a growing body of work supports this view of feeding for comfort, which focuses primarily on the contribution of food and fluids to overall well‐being and quality of life, rather than nutritional needs . Similarly, as the population ages, there is a growing need for patient care in a palliative context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Support for a focus on individual choices and quality of life was strongly indicated by the current study, which further identified the need for clinician self‐care and de‐briefing in this complex clinical area. In the dementia literature in particular, a growing body of work supports this view of feeding for comfort, which focuses primarily on the contribution of food and fluids to overall well‐being and quality of life, rather than nutritional needs . Similarly, as the population ages, there is a growing need for patient care in a palliative context.…”
Section: Discussionmentioning
confidence: 99%
“…This notion of comfort highlights the importance of ceasing feeding if distress is observed, while also highlighting that the goal of feeding is comfort/enjoyment rather than nutrition . Unfortunately, despite being at the heart of complex feeding decisions, older patients and their caregivers may feel they know little about dysphagia and may present with strong emotional responses to the withdrawal or modification of foods and fluids . Furthermore, complex feeding decisions in populations such as individuals with dementia are frequently compounded by questions regarding patient capacity and the individual benefits and risks of feeding options, as well as questions relating to the focus of care including decisions relating to palliation or continued acute medical management …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers may project their own food-related beliefs, attitudes, and values in situations involving others. 137 An example of this is exhibited in the following case study. A young adult nonverbal female with a history of cerebral palsy was admitted to acute care for a second occurrence of aspiration pneumonia.…”
Section: Qolmentioning
confidence: 96%
“…Caregivers may project their own food‐related beliefs, attitudes, and values in situations involving others . An example of this is exhibited in the following case study.…”
Section: Qolmentioning
confidence: 99%